An ampD Gene in Pseudomonas aeruginosa Encodes a Negative Regulator of AmpC β-Lactamase Expression - Langaee, Taimour Yousef (American Society for Microbiology, 1998)
The ampD and ampE genes of Pseudomonas aeruginosa PAO1 were cloned and characterized. These genes are transcribed in the same orientation and form an operon. The deduced polypeptide of P. aeruginosa ampD exhibited more than 60% similarity to the AmpD proteins of enterobacteria and Haemophilus influenzae. The ampD product transcomplemented Escherichia coli ampD mutants to wild-type β-lactamase expression.